ELEMENTS OF LOST WAX CASTING IN PRACTICAL TEACHING - LUKUVKA, Radek (Trends in education, 2012)
The article describes possibilities for aplication elements of lost wax casting especially to practical teaching in subjects as engineering technology eventually also materials science. The article summarizes the elementary principle of issues and it suggets possible and solutions necessary for a practical demonstration of metal casting, molding process and assessment of castings quality. The purpose is to expound the practical issue of metal casting for public from lines of students.
Keywords: lost wax casting; metalurgy.